Strategi Pengembangan Usaha Tanaman Hias di Plantastic Garden, Kota Tangerang Selatan - Nurhandayani, Raditya; Setiyawan, Hery; Setiadi, Agus (Universitas Galuh, 2025)
Plantastic Garden was one of the ornamental plant companies that provided various services, including selling different varieties of ornamental plants, plant rentals, and garden or landscaping services. This study aimed to identify and analyze alternative business development strategies for Plantastic Garden using BMC and BME, the IFE and EFE matrix, and the SWOT matrix. The research was conducted at Plantastic Garden, located in Serpong Utara, South Tangerang City. The study took place from December 2024 to February 2025, involving key informants from within the company. The research method used was a case study. The analytical tools applied included BMC, the IFE Matrix, EFE Matrix, IE Matrix, and SWOT Analysis. The results of this study indicated the addition of a new Customer Segment, namely Event Organizers. The Value Propositions that needed improvement included enhancing the portfolio in landscaping services. The Channels that were added and improved involved creating a website and optimizing e-commerce platforms for selling plant products, such as Shopee and Tokopedia. Customer Relationship improvements could be made by enhancing CRM services for consumers through the implementation of CRM software applications. Revenue Streams could be increased by adding a new business line in Plantastic Garden, specifically by organizing workshops. For Key Resources, additional permanent staff were required for landscape architecture and finance departments. The Key Activities that needed improvement included training for frontline staff to better serve customers, as well as the development of SOPs and digital stock-taking systems. The Key Partnerships that needed enhancement involved collaborations with live-sale sellers. Regarding the Cost Structure, no additional components were necessary, but cash flow monitoring across different business lines was required.